Anticancer activities of pterostilbene-isothiocyanate conjugate in breast cancer cells: involvement of PPARγ. - Kumar Nikhil (Public Library of Science (PLoS), 2014)
Trans-3,5-dimethoxy-4'-hydroxystilbene (PTER), a natural dimethylated analog of resveratrol, preferentially induces certain cancer cells to undergo apoptosis and could thus have a role in cancer chemoprevention. Peroxisome proliferator-activated receptor γ (PPARγ), a member of the nuclear receptor superfamily, is a ligand-dependent transcription factor whose activation results in growth arrest and/or apoptosis in a variety of cancer cells. Here we investigated the potential of PTER-isothiocyanate (ITC) conjugate, a novel class of hybrid compound (PTER-ITC) synthesized by appending an ITC moiety to the PTER backbone, to induce apoptotic cell death in hormone-dependent (MCF-7) and -independent (MDA-MB-231) breast cancer cell lines and to elucidate PPARγ involvement in PTER-ITC action. Our results showed that when pre-treated with PPARγ antagonists or PPARγ siRNA, both breast cancer cell lines suppressed PTER-ITC-induced apoptosis, as determined by annexin V/propidium iodide staining and cleaved caspase-9 expression. Furthermore, PTER-ITC significantly increased PPARγ mRNA and protein levels in a dose-dependent manner and modulated expression of PPARγ-related genes in both breast cancer cell lines. This increase in PPARγ activity was prevented by a PPARγ-specific inhibitor, in support of our hypothesis that PTER-ITC can act as a PPARγ activator. PTER-ITC-mediated upregulation of PPARγ was counteracted by co-incubation with p38 MAPK or JNK inhibitors, suggesting involvement of these pathways in PTER-ITC action. Molecular docking analysis further suggested that PTER-ITC interacted with 5 polar and 8 non-polar residues within the PPARγ ligand-binding pocket, which are reported to be critical for its activity. Collectively, our observations suggest potential applications for PTER-ITC in breast cancer prevention and treatment through modulation of the PPARγ activation pathway.